Aortic Valve Replacement and Penicillin Desensitization in a Patient with Abiotrophia defectiva Aortic Valve Endocarditis - S. Kumar; S. Mahmood; A. Madras; A. Iyer (Case Reports in Cardiology)
Abiotrophia defectiva is an uncommon and insidious yet destructive cause of infective endocarditis preferentially treated with penicillin/gentamicin and often requiring surgical treatment. A 60-year-old man with penicillin anaphylaxis history presented with fevers and a nonspecific constellation of symptoms. He was ultimately diagnosed with bicuspid aortic valve infective endocarditis based on blood cultures growing A.defectiva and echocardiographic evidence of bicuspid aortic valve, severe valvular regurgitation, and 5×7 mm vegetation. Aortic valve replacement and culture yielded penicillin-sensitive A.defectiva. After successful penicillin desensitization, antibiotic therapy was switched from vancomycin/gentamicin to benzylpenicillin. This is the first published case of penicillin desensitization in a patient with A.defectiva-associated infection. Penicillin desensitization, optimal antibiotic therapy, prompt aortic valve replacement, and close collaboration between cardiology and various other specialties were essential in achieving a positive outcome.